Using Linear Regression Model to Predict the Wholesale of the Electric Car in Indonesia: What Can Be Learned from the Model? - Rosyid Ridlo, Al Hakim; Nur F., Soelaiman; Sri, Riani; Yanuar Zulardiansyah, Arief (Springer Nature Singapore Pte Ltd, 2024)
We analyze wholesale datasets from Indonesian Automobile Industry Data for electric cars in Indonesia using statistical analysis to predict the electric cars used in the future. We apply a linear regression approach that adjusts the regression model according to wholesale electric cars between 2020 and 2022, as well as a statistical correlation test and the Wilcoxon test to support the regression result. We find a strong positive relationship for electric cars bought in the future, with a not significantly different population median of the total number of wholesale electric cars. It might be 210 cars estimated per year. Among the regression models, it is more effective for policymakers, as well as car industries. We estimate that there are various reasons and conditions for Indonesian people to buy electric cars inside conventional ones.